MPT0B098, a Microtubule Inhibitor, Suppresses JAK2/STAT3 Signaling Pathway through Modulation of SOCS3 Stability in Oral Squamous Cell Carcinoma. - Hsuan-Yu Peng; Yun-Ching Cheng; Yuan-Ming Hsu; Guan-Hsun Wu; Ching-Chuan Kuo; Jing-Ping Liou; Jang-Yang Chang; Shiow-Lian Catherine Jin; Shine-Gwo Shiah (PLoS ONE, 2016)
Microtubule inhibitors have been shown to inhibit Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signal transduction pathway in various cancer cells. However, little is known of the mechanism by which the microtubule inhibitors inhibit STAT3 activity. In the present study, we examined the effect of a novel small-molecule microtubule inhibitor, MPT0B098, on STAT3 signaling in oral squamous cell carcinoma (OSCC). Treatment of various OSCC cells with MPT0B098 induced growth inhibition, cell cycle arrest and apoptosis, as well as increased the protein level of SOCS3. The accumulation of SOCS3 protein enhanced its binding to JAK2 and TYK2 which facilitated the ubiquitination and degradation of JAK2 and TYK2, resulting in a loss of STAT3 activity. The inhibition of STAT3 activity led to sensitization of OSCC cells to MPT0B098 cytotoxicity, indicating that STAT3 is a key mediator of drug resistance in oral carcinogenesis. Moreover, the combination of MPT0B098 with the clinical drug cisplatin or 5-FU significantly augmented growth inhibition and apoptosis in OSCC cells. Taken together, our results provide a novel mechanism for the action of MPT0B098 in which the JAK2/STAT3 signaling pathway is suppressed through the modulation of SOCS3 protein level. The findings also provide a promising combinational therapy of MPT0B098 for OSCC.